2015
DOI: 10.5152/npa.2015.7565
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Onset Panic Disorder: Incidence, Comorbidity and Associated Factors

Abstract: Introduction: The present study aimed to investigate the incidence rate of pregnancy-onset panic disorder (POPD) among Turkish pregnant women using a diagnostic interview. Additionally, we examined whether the independent socio-demographic or clinical risk factors were associated with the risk of panic disorder in these women.Methods: The study sample comprised 1475 consecutive pregnant women who presented to the obstetric outpatient clinics of two research centers. The rate of POPD in these participants was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] The assumption that reproductive life events may contribute to this higher prevalence in women via onset or recurrence of anxiety disorders has been supported by several studies. [5][6][7][8] Panic disorder is an anxiety disorder that is frequently observed in the perinatal period. It has been reported that panic disorder during pregnancy is associated with lower birth weight and shorter gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The assumption that reproductive life events may contribute to this higher prevalence in women via onset or recurrence of anxiety disorders has been supported by several studies. [5][6][7][8] Panic disorder is an anxiety disorder that is frequently observed in the perinatal period. It has been reported that panic disorder during pregnancy is associated with lower birth weight and shorter gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these studies, a prospective study that was conducted in Turkey showed that the severity of panic disorder symptoms declined from pregnancy to 6 weeks after birth, which could be explained by psychosocial influences (E.g., financial problems, an increased workload, or reduced sleeping) and hormonal changes mainly estrogen, progesterone, and cortisol [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the estimated prevalence of PD during pregnancy varies between studies, and it ranges from 0.2 % to 7.0 %. For example, in Sweden it was 0.2% [ 18 ], in Hungary it was 0.5% [ 19 ], in Italy it was 7.0% [ 20 ], and 1.3% among Turkish pregnant women [ 15 ]. This discrepancy in prevalence may be due to different assessment tools used by the researchers, different settings, and cultural differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that pregnancy may be a specific risk factor for the occurrence and/or exacerbation of anxiety disorders. A possible reason for the occurrence of anxiety during pregnancy could be traced back to experienced sudden changes during pregnancy, such as increased heart and respiratory rates, chest tightness, and shortness of breath (31).…”
Section: Prevalence Of Pregnancy-related Anxietymentioning
confidence: 99%